Observations about the status of complementary and alternative medicine in Polish law - Lyszczyna, Anna (The Opole Studies in Administration and Law, 2022)
Complementary and alternative medicine are therapeutic methods not included in academic (conventional) medicine. In recent years, there has been a noticeable increase in demand for paramedical services. In Poland, they have no separate legal regulation, so it is not clear whether they should be treated as an ‚ordinary’ service or a medical service.